Understanding and Treating Military Sexual Trauma - Zaleski, Kristen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This thorough analysis of sexual assault in the military examines the scope of this long-neglected issue using a lens informed by modern day attachment and trauma theories. Starting with an overview of sexual violence during wartime, it details the cultural and organizational aspects of military life--and entrenched ideas about war and masculinity--that compound military sexual trauma (MST) and reinforce barriers to treatment for women and men. The book's second half reviews empirically-supported interventions for MST survivors, recommending therapy that attends to somatic, implicit, relational based aspects of trauma processing rather than the conventional cognitive therapies currently funded in many military mental health programs. This powerful presentation, which includes sobering quotes from survivors, also raises serious questions about meeting veterans' needs, training for on- and off-base clinicians, and government funding.  Included in the coverage:  The history of sexual violence in war. Trauma and recovery in military culture. The neurobiology of trauma. A military rape sub-culture hypothesis about the hidden sexual assault epidemic. How military culture and military law affect the immediate aftermath of MST. Treating the trauma and not just the memory. Questions the “one size fits all” approach of many trauma therapies for MST. Top-down cognitive-based treatment for MST. Body-based bottom-up psychotherapy for MST.   Understanding and Treating Military Sexual Trauma belongs in the libraries of private practice clinicians and government psychologists. It provides cutting edge knowledge to practitioners in training, such as graduate-level students studying psychology and social work. Its dual emphasis on military culture and women's lives will appeal to students in gender studies, sociology and program planning disciplines. .
Part I: Understanding Military Sexual Trauma -- The History of Sexual Violence in War -- The Military Rape Sub-Culture Hypothesis -- Trauma and Recovery Within Military Culture -- Rape and Roll Call: How military culture and military law affect the immediate aftermath of Military Sexual Trauma -- Vulnerabilities in Military Rape Culture -- Part II: Treating Military Sexual Trauma -- Treating the Trauma of Military Sexual Assault (Not just the memory) -- Top-Down Cognitive Based Interventions for Military Sexual Trauma -- Body Based Bottom-Up Psychotherapy for Military Sexual Trauma.
Keywords: Sexual behavior; Sexual psychology; Psychotherapy; Counseling; Sexual Behavior; Psychotherapy and Counseling